Transformation and continuity in urban space the smartphone as a companion to digital teaching and learning processes in extracurricular learning settings - Zimmermann, Julian Claudius (Journal of educational media, memory, and society, 2019)
The progressive digitization of society is irreversibly changing education. Specialists in teaching methodologies are having to address questions raised by the digital revolution in schools and develop appropriate training for teachers. This article responds to this revolution by proposing that smartphones be used to support digital teaching and learning processes in extracurricular learning settings. Specifically, it presents digital city tours as potential tools designed to help learners to explore the urban space integral to their living environment, recognize its historical dimension, and work on this dimension by developing digital narratives. The smartphone is understood here as a tool that makes it possible for learners to experience history and that encourages them to develop learning skills.